(3GdbGfhf GdYGe ddhXja GdYehej s - (3aDGO (B, (3MLQjs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2006)
(3jYJHQ gPG GdcJGH LRA ef SdSdI GdbhGfjf GdEOGQjI jJfGhd eLehYI ef GdbhGfjf hGdJTQjYGJ GdNGUI HGdhXja GdYehej s
Keywords: (3GdbGfhf GdEOGQjs; (3GdhXGFa(B- (3bhGfjf hJTQjYGJ s